⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ 3 a + 4 x = 6 3 b + 4 y = 1 a 2 + b 2 = 1 x 2 + y 2 = 1
Given that a , b , x and y satisfy the system of equations above, find the value of a x + b y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
nice job !!
Nice observation!
I was wanting to use complex numbers to solve this :)
Nice one. Thanks.
thank you !!!!!!!!!!!!!!!!
you are really BRILLIANT!!
Manrique's solution is certainly more elegant than mine was, but here goes:
3 a + 4 y = 6
Add 3 b + 4 y = 1 into the first equation, one would get:
3 ( a + b ) + 4 ( x + y ) = 7
Squaring and expanding, one would yield (ive skipped a few steps, but I think the general idea is there) :
9 ( a 2 + b 2 ) + 1 6 ( x 2 + y 2 ) + 2 4 ( a x + b y ) + 6 a ( 3 b + 4 y ) + 8 x ( 3 b + 4 y ) = 4 9
Since a 2 + b 2 = 1 , x 2 + y 2 = 1 , 3 b + 4 y = 1 , 3 a + 4 x = 6 :
2 4 ( a x + b y ) = 4 9 − 1 6 − 9 − 2 ( 6 )
a x + b y = 2 4 1 2 = 0 . 5
Problem Loading...
Note Loading...
Set Loading...
We need to generate the a x and b y terms for the solution. There are many ways to do that, but the requested one is to square the first two equations:
( 3 a + 4 x ) 2 = 6 2 ⇒ 9 a 2 + 2 4 a x + 1 6 x 2 = 3 6
( 3 b + 4 y ) 2 = 1 2 ⇒ 9 b 2 + 2 4 b y + 1 6 y 2 = 1
Adding up the two results:
9 ( a 2 + b 2 ) + 2 4 ( a x + b y ) + 1 6 ( x 2 + y 2 ) = 3 7
and substituing the other two equations:
9 + 2 4 ( a x + b y ) + 1 6 = 3 7 ⇒ 2 5 + 2 4 ( a x + b y ) = 3 7 ⇒ 2 4 ( a x + b y ) = 1 2
Then, a x + b y = 2 1